KOMPETENSI PROFESIONAL GURU (Studi Pada Program Dual Mode System Fakultas Ilmu Tarbiyah dan Keguruan IAIN Ar Raniry Banda Aceh Tahun 2013) - Musa Al-Fadhil (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2015)
Increased professional competence of teachers is an activity that must be done regularly and continuously. Dual Mode System as one of the programs at the Faculty of Science Tarbiyah and Teachers are expected to be reliable and professional. Research method using qualitative approach, research subject is team of program organizer Dual Mode System, Lecturer, and student. Data collection with observation techniques and questionnaires. The results show that the Dual Mode System Program has been working to maximally improve the professional competence of teachers. The learning system is applied by combining self-learning and face-to-face learning. Teacher as a student has been able to play an active role in the learning activities undertaken. This can be seen from the enthusiasm of the students following the lectures. However, attempts to improve the professional competence of teachers through the Dual Mode System program encountered several obstacles and obstacles, such as not routine lectures, lack of literature sources and lack of function of academic advisors lecturers.